SIMULASI STRESS PADA MESIN PENIRIS MINYAK - Indra, Elvan; Darren Halim, Alessandro; Ilham Sekayu, Muhammad; Rosehan (POROS, 2023)
Every food that is frequently consumed nowadays usually uses cooking oil as a frying tool. Indonesian people, both in urban and rural areas, consume fried foods in their daily lives. Therefore, by designing an oil drainer, we can overcome the problem in terms of time in draining oil from fried onions. In this oil dryer there are main components to drive the oil dryer system in the form of perforated baskets, shafts, AC electric motors, v-belts, pulleys, bearings, and table. The material used in this oil dryer uses food grade materials, for the safety and health of users of this oil dryer. The oil dryer has a capacity of 3 kg at one time the frying of fried onions is then calculated to find out which material is suitable for use in the oil slicer, then performs a simulation to determine the strength of the material selection used.